2021
DOI: 10.6061/clinics/2021/e2251
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor mutation burden and epidermal growth factor receptor inhibitor history with survival in patients with metastatic stage III/IV non-small-cell lung cancer: A retrospective study

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. However, factors associated with the survival of patients with advanced non-small-cell lung cancer (NSCLC) who received only hospice care are largely unclear. In this study, we aimed to determine the prognostic factors correlated with survival in patients with advanced NSCLC who had undergone hospice care only. METHODS: A total of 102 patients with recurrent stage III/IV NSCLC after traditional treatment failure were investigated. Survival wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Numerous investigations have suggested that peripheral lung neoplasm has a better prognosis, both in SCC and ADCs. [ 20 23 ] But there are still controversial definitions among different studies about tumor locations. Different locations in lung cancer are associated with the distribution of lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous investigations have suggested that peripheral lung neoplasm has a better prognosis, both in SCC and ADCs. [ 20 23 ] But there are still controversial definitions among different studies about tumor locations. Different locations in lung cancer are associated with the distribution of lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Primary location in lung tumor has prognostic value, suggesting that patients with peripheral-type lung cancer and central-type lung cancer have different prognoses. Numerous investigations have suggested that peripheral lung neoplasm has a better prognosis, both in SCC and ADCs [20–23] . But there are still controversial definitions among different studies about tumor locations.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicopathological features differ between peripherally and centrally located primary lung cancers, with central location being a significant poor prognostic factor in both adenocarcinomas and squamous cell carcinomas (8-10). Moreover, in inoperable stage III/IV advanced lung cancer patients, central location of the tumor was an independent poor prognostic factor (11). These findings revealed that the malignant potential of tumors generated in the central region may contribute to poor prognosis.…”
Section: Discussionmentioning
confidence: 79%
“…More EGFR mutations have been reported in noncavitary lung ADC, with a mutation rate of 47.3% and 33.6%, respectively [45], providing more treatment modalities, which in turn gives a better prognosis. Lan et al 2021 [42] revealed a significantly shorter survival duration in patients with cavitary adenocarcinoma (p < 0.001), with a 5-year survival rate of 67.7% and a median survival time of 61.2 months. Patients without cavitary formation had a 5-year survival rate of 80.8%.…”
Section: Discussionmentioning
confidence: 96%
“…The primary site of the lung tumour holds prognostic significance, implying that patients with peripheral-type and central-type lung cancer exhibit distinct prognoses. Several studies have suggested that peripheral lung tumours offer a more favourable prognosis, regardless of whether they are squamous cell carcinomas or adenocarcinomas [41][42][43].…”
Section: Discussionmentioning
confidence: 99%